SAR of a birdcage coil with variable number of rungs at 300 MHz. (March 2016) - Martin, R.; Vazquez, J.F.; Marrufo, O.; Solis, S.E.; Osorio, A.; Rodriguez, A.O.
Graphical abstract: Highlights: SAR study of a birdcage coil with a variable number of rung. Global SAR remains practically constant regardless the number of rungs. Experimental validation of numerical simulation of SAR via the S-parameter. Fusion images of SAR distributions and anatomical images of a rat's brain. Abstract: The specific absorption rate produced in a rat's brain phantom inside of quadrature birdcage coil as a function of the rung number was studied at 300 MHz. Electromagnetic field simulations and specific absorption rate and loss return responses were performed using a rat's brain phantom weighing 100 mg. To assure optimal simulations and to evaluate coil performance, S-parameters were simulated and compared with experimentally data. Simulations showed that magnetic field uniformity improves and that electric field is increased with the number of rungs. Specific absorption rate and temperature values obtained from axial bi-dimensional maps increase as the number of rungs grows. These results corroborated very well with published data. A quadrature 16-rung birdcage coil was developed for comparison and phantom images were acquired to show its feasibility. The presented approach yields information on specific absorption rate allowing to previously develop RF coils and their possible effects on the biological sample.